Methodology of National Health and Morbidity Survey (NHMS): adolescent health, Malaysia 2022 - Lim, Kuang Kuay; Maznieda Mahjom; S Maria Awaluddin; Noor Syaqilah Shawaluddin; Tuan Mohd Amin Tuan Lah; Hamizatul Akmal Abd Hamid; Muhammad Fadhli Mohd Yusoff; Tan, Lee Ann; Noor Ani Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Malaysia, the adolescent health surveys conducted in 2012 and 2017 revealed an increasing trend of adolescent health risk behaviours and protective factors. This current article aims to describe the methodology of the National Health and Morbidity Survey (NHMS) 2022: Adolescent Health in Malaysia. The current nationwide cross-sectional survey of Malaysian secondary school students used multistage stratified sampling to select 240 nationally representative schools. This survey is conducted from June to July 2022 among the students in forms 1, 2, 3, 4, and 5 in all Malaysian states by 34 data collection teams. A validated self-administered questionnaire is used, similar to those used in the NHMS 2012 and NHMS 2017. The quality control is done twice, once at the field level and once at the central level. Sample weighting and analysis are conducted using SPSS statistical software version 28.0. A total of 239 out of 240 randomly selected schools with 33,523 adolescents are involved in this study (overall response rate is 89.0%). The distribution of state, sex, and form among adolescents is almost equal. Compared to both previous adolescent health surveys using the same methodology and approaches, the overall response rates for NHMS 2017 and NHMS 2012 are 89.2% and 88.8%, respectively. The implementation of NHMS 2022 has employed an acceptable methodology for a survey of the adolescent population. This reliable data provides national estimates for adolescent health risk behaviours and protective factors. The survey allows the relevant authorities to carried out further improve the health status of adolescents in Malaysia.